2020
DOI: 10.1186/s13063-019-3991-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the efficiency of recruitment to stroke rehabilitation randomised controlled trials

Abstract: Introduction: Randomised controlled trials (RCTs) that fail to meet their recruitment target risk increasing research waste. Acute stroke RCTs experience notable recruitment issues. The efficiency of recruitment to stroke rehabilitation RCTs has not been explored. Aims and objectives: To explore recruitment efficiency and the trial features associated with efficient recruitment to stroke rehabilitation RCTs. Methods: A systematic review of stroke rehabilitation RCTs published between 2005 and 2015 identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 63 publications
0
40
1
Order By: Relevance
“…Well-designed randomised controlled trials (RCTs) provide the highest level of quality for assessing the efficacy of interventions [ 46 ]. However, achieving recruitment targets can be difficult, leading to extended study timeframes, additional costs or wastage of valuable research money when studies fail to reach targets [ 47 ]. As an alternate strategy, clinical registries may provide vehicles to facilitate recruitment for clinical trials, particularly trials recruiting community-dwelling stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Well-designed randomised controlled trials (RCTs) provide the highest level of quality for assessing the efficacy of interventions [ 46 ]. However, achieving recruitment targets can be difficult, leading to extended study timeframes, additional costs or wastage of valuable research money when studies fail to reach targets [ 47 ]. As an alternate strategy, clinical registries may provide vehicles to facilitate recruitment for clinical trials, particularly trials recruiting community-dwelling stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest challenge we faced was recruitment of participants however our difficulties are not unique and indeed our recruitment of two participants per month is in line with a recent systematic review. 26 Similarly, the attendance levels seen within the group intervention are reflective of attendance levels for other face-toface group therapy interventions. 25,27 Although initial contact on the stroke unit proved challenging and resulted in difficulties in recruitment, conversely a delayed approach in some cases resulted in the intervention being delivered after the time that it was reported as most needed.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Invitation emails, including the information sheet and study protocol, were sent to 177 stroke rehabilitation trialists identified by applying the purposeful sampling criteria to authors contacted during an earlier systematic review. 20 Initially 22 trialists responded, indicating an interest in participation, however, one trialist later declined without providing a reason and another was excluded as they had not conducted a stroke rehabilitation trial within the last 10 years. Interviews were conducted between November 2017 and January 2018.…”
Section: Methodsmentioning
confidence: 99%
“…2 Stroke rehabilitation trials are complex and may experience increased recruitment difficulties due to the involvement of multidisciplinary teams, the variance in settings and the variety of interventions used. 11 Despite notable difficulties recruiting stroke survivors, and limited improvement over the past two decades, 3,12 little research has focused on trialists’ perspectives of recruitment for stroke trials. Trialist’s have wealth of recruitment knowledge that they often do not get the chance to share widely.…”
Section: Introductionmentioning
confidence: 99%